Ratiometric Single‐Molecule FRET Measurements to Probe Conformational Subpopulations of Intrinsically Disordered Proteins. Issue 1 (11th March 2020) - Nasir, Irem; Bentley, Emily P.; Deniz, Ashok A.
Abstract: Over the past few decades, numerous examples have demonstrated that intrinsic disorder in proteins lies at the heart of many vital processes, including transcriptional regulation, stress response, cellular signaling, and most recently protein liquid‐liquid phase separation. The so‐called intrinsically disordered proteins (IDPs) involved in these processes have presented a challenge to the classic protein "structure‐function paradigm, " as their functions do not necessarily involve well‐defined structures. Understanding the mechanisms of IDP function is likewise challenging because traditional structure determination methods often fail with such proteins or provide little information about the diverse array of structures that can be related to different functions of a single IDP. Single‐molecule fluorescence methods can overcome this ensemble‐average masking, allowing the resolution of subpopulations and dynamics and thus providing invaluable insights into IDPs and their function. In this protocol, we describe a ratiometric single‐molecule Förster resonance energy transfer (smFRET) routine that permits the investigation of IDP conformational subpopulations and dynamics. We note that this is a basic protocol, and we provide brief information and references for more complex analysis schemes available for in‐depth characterization. This protocol covers optical setup preparation and protein handling and provides insights into experimental design and outcomes, together with background information about theory and a brief discussion of troubleshooting. © 2020 by John Wiley & Sons, Inc. Basic Protocol : Ratiometric smFRET detection and analysis of IDPs Support Protocol 1 : Fluorophore labeling of a protein through maleimide chemistry Support Protocol 2 : Sample chamber preparation Support Protocol 3 : Determination of direct excitation of acceptor by donor excitation and leakage of donor emission to acceptor emission channel